Educaplay for Selective Listening Instruction: Students Benefits and Challenges in an EFL Classroom - Mia Aulia; Dila Charisma; Fitri Aprianti (Journal of English Language and Education, 2026)
Listening is one of the most challenging language skills for EFL learners, particularly in selective listening activities that require students to identify specific information from spoken texts. To address this issue, interactive digital media such as Educaplay can provide engaging learning experiences and support listening comprehension. This study aimed to explore the benefits experienced by eighth-grade students when using Educaplay in selective listening activities. A qualitative case study design was selected because it enabled an in-depth exploration of students’ learning experiences, perceptions, and interactions within a real classroom context. The study involved 39 eighth-grade students at a junior high school in Kuningan Regency, West Java. Data were collected through classroom observations, semi-structured interviews, student reflections, and field notes, and analyzed using thematic analysis. The findings revealed that Educaplay enhanced students’ engagement, motivation, confidence, vocabulary development, and selective listening abilities. Its interactive, game-based features promoted active participation and improved students’ ability to identify specific information from spoken texts while fostering time management and critical thinking. Although internet connectivity, audio comprehension, and device limitations posed challenges, students generally responded positively, indicating that Educaplay is an effective medium for supporting selective listening instruction in EFL classrooms.